2020
DOI: 10.1126/science.aaz2121
|View full text |Cite
|
Sign up to set email alerts
|

The N-glycome regulates the endothelial-to-hematopoietic transition

Abstract: Definitive hematopoietic stem and progenitor cells (HSPCs) arise from the transdifferentiation of hemogenic endothelial cells (hemECs). The mechanisms of this endothelial-to-hematopoietic transition (EHT) are poorly understood. We show that microRNA-223 (miR-223)–mediated regulation of N-glycan biosynthesis in endothelial cells (ECs) regulates EHT. miR-223 is enriched in hemECs and in oligopotent nascent HSPCs. miR-223 restricts the EHT of lymphoid-myeloid lineages by suppressing the mannosyltransferase alg2 a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 28 publications
2
25
0
Order By: Relevance
“…In contrast, C6 cells had high expression of key hemogenic and HSC marker genes, including gata2b , meis1b , and myb , as well as expression of lineage-restricted genes indicative of multipotent priming, such as gata1a (erythroid) ( Gutiérrez et al, 2020 ; Galloway et al, 2005 ), ikzf1 (lymphoid) ( Huang et al, 2019 ; Willett et al, 2001 ), and coro1a and csf1rb (myeloid) ( Li et al, 2012 ; Carstanjen et al, 2005 ; Song et al, 2004 ); we consequently designated cluster C6 as hemogenic endothelial cells generating HSCs (HE/HSCs). The C4 cells expressed erythroid and lymphoid markers with low expression of myeloid markers, suggesting this population is analogous to the recently described lympho-erythroid-primed progenitor (LEP) in zebrafish ( Kasper et al, 2020 ). Cells with LMP expression profile occurred in two clusters: (1) an LMP population with higher macrophage marker expression ( csf1ra, irf8, mfap4 , and mpeg1.1 ) ( Rojo et al, 2019 ; Li et al, 2011 ; Zakrzewska et al, 2010 ) (LMP-M, C8) and (2) an LMP population with higher granulocyte marker expression ( mpx and lyz ) ( Hall et al, 2007 ; Renshaw et al, 2006 ) (LMP-G; C9).…”
Section: Resultssupporting
confidence: 66%
See 1 more Smart Citation
“…In contrast, C6 cells had high expression of key hemogenic and HSC marker genes, including gata2b , meis1b , and myb , as well as expression of lineage-restricted genes indicative of multipotent priming, such as gata1a (erythroid) ( Gutiérrez et al, 2020 ; Galloway et al, 2005 ), ikzf1 (lymphoid) ( Huang et al, 2019 ; Willett et al, 2001 ), and coro1a and csf1rb (myeloid) ( Li et al, 2012 ; Carstanjen et al, 2005 ; Song et al, 2004 ); we consequently designated cluster C6 as hemogenic endothelial cells generating HSCs (HE/HSCs). The C4 cells expressed erythroid and lymphoid markers with low expression of myeloid markers, suggesting this population is analogous to the recently described lympho-erythroid-primed progenitor (LEP) in zebrafish ( Kasper et al, 2020 ). Cells with LMP expression profile occurred in two clusters: (1) an LMP population with higher macrophage marker expression ( csf1ra, irf8, mfap4 , and mpeg1.1 ) ( Rojo et al, 2019 ; Li et al, 2011 ; Zakrzewska et al, 2010 ) (LMP-M, C8) and (2) an LMP population with higher granulocyte marker expression ( mpx and lyz ) ( Hall et al, 2007 ; Renshaw et al, 2006 ) (LMP-G; C9).…”
Section: Resultssupporting
confidence: 66%
“…Most cells resided in clusters C1, C2, and C3 and predominantly expressed erythroid markers, which we broadly designated as erythroid progenitors (EryPs). Together, our identified clusters encompass the range of HSPC-associated progenitor traits ( Hou et al, 2020 ; Kasper et al, 2020 ; Zhu et al, 2020 ; Xue et al, 2019 ; Zhou et al, 2016 ), here resolved into distinct progenitor clusters.…”
Section: Resultsmentioning
confidence: 83%
“…In order to explain the previously observed increase in HSPC numbers in microRNA miR-223 mutants [117], the authors compared transcriptomic data on sorted miR-223 reporter-positive endothelial cells from wildtype and miR-223 null embryos. They observed that several of the most significantly upregulated genes in the mutants, that also themselves contain miR-223 binding sites in the RNA transcript, were enzymes that regulate N-glycosylation of proteins [118]. Extraction and mass spectrometry of glycoproteins from sorted zebrafish endothelial cells showed that the N-glycan landscape was dysregulated, with a shift from high mannose-to high sialic acid-containing N-glycosylated proteins, and that the metalloprotease Adam10a was one such affected protein in zebrafish that regulates EHT.…”
Section: Extrinsic Cues: Metabolic Hormonal and Inflammatory Signals 41 Glucose And Other Metabolitesmentioning
confidence: 99%
“…Furthermore, FGF signaling has been shown to promote TGF-β mediated EndoMT via regulation of let-7 miRNA expression (Chen et al, 2012) but to limit it via miR-20 (Correia et al, 2016). Consistent with this hypothesis, endothelial expression of Dicer -the protein responsible for miRNA pre-processing -is required for angiogenesis (Suárez et al, 2008) and miRNAs have also recently been reported to regulate endothelial-to-hematopoietic transition (Kasper et al, 2020). Thus, the interrelationship between miRNA species in ECs and their combined effect on EndoMT progression warrant further study.…”
Section: Micrornamentioning
confidence: 84%